Persistencia de errores conceptuales en el estudio del equilibrio químico - Furió-Mas, Carles; Ortiz, Elena (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper exposes the existence of certain conceptual errors in the study of chemical equilibrium, lack of differentiation between full chemical reaction and equilibrium compartimentation of equilibrium,.., and, in particular, the strong persistance of the error of mass -concentration oí substances. For it, examples were taken from two different groups: Pre -University course students and teachers students.